Impact of cardiovascular events on primary and hospital care costs: findings from UK Biobank study. (3rd October 2022) - Zhou, J; Wu, R; Williams, C; Emberson, J; Reith, C; Keech, A; Robson, J; Wilkinson, K; Armitage, J; Collins, R; Gray, A; Simes, J; et al.
Abstract: Background: Need for primary and secondary healthcare increases following cardiovascular disease (CVD) events but there is no data on comparative increases in costs. Purpose: To estimate annual primary care and hospital inpatient costs associated with key CVD and other adverse events using the UK Biobank (UKB) individual participant data. Methods: UKB participants with linked primary care data (192, 983 participants) or hospital inpatient episodes data (all 501, 807 participants) contributed data to this study. The three categories of primary care services (patient consultations, diagnostic and monitoring tests, prescription medications), and hospital episodes were costed (2020 UK£) using the NHS England reference costs. Annual primary care costs and, separately, annual hospital inpatient costs were modelled as functions of participant characteristics at entry (socio-demographic, clinical, prior diseases) and time-updated first occurrences of myocardial infarction, stroke, coronary revascularization, incident cancer, incident diabetes, vascular death and non-vascular death during follow-up (p-value <0.01 in stepwise covariate selection). One-part generalized linear regression model (GLM) with Poisson distribution and identity link function was used for primary care costs, and two-part model was used for inpatient costs (part 1: logistic regression models probability of incurring costs; part 2: GLM with Poisson distribution and identity link function models costs conditional on incurring any). Separate models were fitted among participants with and without previous CVD at entry into UKB. Results: Most adverse events were associated with excess primary care and hospital inpatient costs. Compared to people without previous CVD, people with previous CVD had on average larger excess primary care and hospital inpatient costs in years with myocardial infarction, stroke and vascular death; but similar excess costs in years with other events. Among both people without and with previous CVD, the excess annual primary care costs were less than 7% of the excess annual hospital inpatient costs for vascular events (Table). However, following diabetes diagnosis the excess annual primary care costs were higher than the excess annual hospital inpatient costs (Table). Conclusions: These excess primary and hospital care costs associated with CVD events could inform assessments of interventions and policies to reduce CVD risks in UK. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): UK National Institute for Health Research (NIHR) Health Technology Assessment (HTA) Programme, UK Medical Research Council (MRC), British Heart Foundation